Rechte des Körpers: Juristische, philosophische und theologische Perspektiven (De Gruyter, 2022)
The volume asks about the role of the body in law. Representatives of philosophy, theology, and jurisprudence examine the physical, material, or natural (pre-)conditions of law, which law does not cover or covers only to a degree.